2014
DOI: 10.4049/jimmunol.1400630
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Two Temporal Phases of HIV-1 Transfer from Primary Langerhans Cells to T Cells: The Role of Langerin

Abstract: Epidermal Langerhans cells (eLCs) uniquely express the C-type lectin receptor langerin in addition to the HIV entry receptors CD4 and CCR5. They are among the first target cells to encounter HIV in the anogenital stratified squamous mucosa during sexual transmission. Previous reports on the mechanism of HIV transfer to T cells and the role of langerin have been contradictory. In this study, we examined HIV replication and langerin-mediated viral transfer by authentic immature eLCs and model Mutz-3 LCs. eLCs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 59 publications
6
76
0
Order By: Relevance
“…The application of TNF-a-containing supernatants would be expected to induce partial MDDC maturation and delay the degradation of HIV p24 Ag in virus-containing compartments, which could confound using this test as a measure of de novo HIV replication. However, this was anticipated by performing the intracellular p24 Ag assays at 96 hpi, long after such Ag has decayed to negligible levels in mature MDDCs, as previously shown with much more potent inducing stimuli (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of TNF-a-containing supernatants would be expected to induce partial MDDC maturation and delay the degradation of HIV p24 Ag in virus-containing compartments, which could confound using this test as a measure of de novo HIV replication. However, this was anticipated by performing the intracellular p24 Ag assays at 96 hpi, long after such Ag has decayed to negligible levels in mature MDDCs, as previously shown with much more potent inducing stimuli (40).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation could be enhanced persistence of the HIV inoculum, but we and others have previously shown this is degraded in MDDCs by 24 hpi. Therefore, p24ag present in MDDCs after 48 hpi represents de novo replication as shown by AZT inhibition (31,40,41). Furthermore, enhanced persistence of HIV inoculum would not explain the increase in HIV cDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Increased T1N incidence following the Pandemrix® vaccination was 15 first seen in Northern Europe [13][14][15][16][17][18][19][20] with 8-fold increase in incidence in (0.79/100,000 to 16 6.3/100,000) in children. The specificity was striking, as increased T1N was later detected in all 17 countries where Pandemrix® was used, whereas countries using other pH1N1 vaccine brands 18 did not detect vaccination-associated increases in incidence [13][14][15][16][17][18][19][20][21][22] . is defined by antigen presentation, mediated through specific T cell receptor chains, and 27 modulated by influenza-A as a critical trigger.…”
mentioning
confidence: 99%
“…Human immunodeficiency virus type 1(HIV-1) is recognized by a variety of CLRs, including DC-SIGN, MMR, and langerin (18,19). While initial studies suggested that recognition by langerin resulted in uptake and degradation of HIV-1 in Birbeck granules (20), recent studies show that langerin-mediated uptake can facilitate transfer of the virus from DC to T cells, in a manner analogous to that reported for DC-SIGN (21)(22)(23)(24)(25). This occurs via two routes, either via plasma membrane-linked (neutral pH) intracellular compartments or via receptors for enhanced de novo replication in DC, thus facilitating virus transmission.…”
mentioning
confidence: 99%